2019
DOI: 10.1093/infdis/jiz580
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-13 in Atherosclerotic Plaque Is Increased by Influenza A Virus Infection

Abstract: Background Influenza virus infection triggers acute cardiovascular events. Several studies have demonstrated that influenza A virus infection was associated with immune cell influx and increased production of inflammatory cytokines in the atherosclerotic plaque lesion, but the underlying mechanism for these findings is not clear. Methods We examined the expression levels of matrix metalloproteinases (MMPs) by influenza A viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…An in vitro study using HUVEC cells has shown that influenza virus infection increases the expression of MMP9. Another study has shown that the expression of MMP-13 is increased in the atherosclerotic plaques of Apoe -/mice infected with influenza A virus (129). These studies suggest that influenza virus infection-induced inflammatory mediators may increase plaque destabilization and rupture, leading to MI.…”
Section: Effect Of Influenza Virus Infection On Plaque Rupturementioning
confidence: 90%
“…An in vitro study using HUVEC cells has shown that influenza virus infection increases the expression of MMP9. Another study has shown that the expression of MMP-13 is increased in the atherosclerotic plaques of Apoe -/mice infected with influenza A virus (129). These studies suggest that influenza virus infection-induced inflammatory mediators may increase plaque destabilization and rupture, leading to MI.…”
Section: Effect Of Influenza Virus Infection On Plaque Rupturementioning
confidence: 90%
“…The correlation between the increase in the expression level of MMP-1, MMP-3, and MMP-12 and plaque instability and cardiovascular disease progression were demonstrated clearly [149]. In the cells infected with influenza a virus, an increase in MMP-13 within 3 days of infection was found [152]. MMP-13 expression, mediated by influenza a virus via p38 mitogen activated protein kinase, was found to destabilize the susceptible arterial plaques triggering cardiovascular events eventually [152].…”
Section: Mps In Cardiovascular Diseasesmentioning
confidence: 97%
“…Studies on human cells infected with influenza A virus showed an increase of MMP-13 expression, which may partly explain the destabilization of atherosclerotic plaques. Analysis of the corresponding changes in the ApoE-deficient mouse model has shown that the increase of MMP-13 expression is due to activation of the p38 mitogen-activated protein kinase signaling pathway [119]. Increased MMP-7 activity can be connected with the apoptosis of VSMCs in the fibrous cap and lesion destabilization [120].…”
Section: Mmps In Plaque Activation and Destabilizationmentioning
confidence: 99%